Rapid methods for the separation of natural mixtures of beauverolides, cholesterol acyltransferase inhibitors, isolated from the fungus Isaria fumosorosea - Šimčíková, Daniela; Tůma, Petr; Jegorov, Alexandr; Šimek, Petr; Heneberg, Petr (Journal of separation science, 2020)
Beauverolides (beauveriolides) are abundant, biologically active cyclodepsipeptides produced by many entomopathogenic fungi, including those that are used as biopesticides. Beauverolides act as cholesterol acyltransferase inhibitors in humans; thus, their mode of action has been the subject of pharmacological and clinical research. The cost-effective analytical methods are needed for fast, routine laboratory analysis of beauverolides. We isolated beauverolides from the fungal strain Isaria fumosorosea PFR 97-Apopka and opened the rings of the isolated beauverolides using a pyridine alkaline medium. We separated fractions of cyclic and linearized beauverolides by thin-layer chromatography, and found the chloroform-acetate (9:1, v/v) and chloroform-acetonitrile-acetate (8:1:1, v/v/v) mobile phases, respectively, to be the most efficient. We examined all the fractions by liquid chromatography-mass spectrometry using ion trap and Orbitrap high resolution mass spectrometry. For rapid screening of the contents of cyclic, and, particularly, linearized beauverolides, we developed a novel analytical method that consisted of using capillary electrophoresis coupled with contactless conductivity detection. Furthermore, we improved the separation of the peptides by applying capillary micellar electrokinetic chromatography with the N-cyclohexyl-2-aminoethanesulfonic acid:SDS:NaOH buffer, pH 9.8 as the background electrolyte. The described novel methods allow fast and cost-effective separation of chemically related groups of beauverolides.
Keywords: hmotnostní spektrometrie; Chromatography, Liquid; Depsipeptides; lidé; anticholesteremika; Mass Spectrometry; chromatografie kapalinová; Humans; Anticholesteremic Agents; depsipeptidy; Cordyceps